Methodology investigations for the synthesis of biologically important nitrogen-containing heterocycles - Dobah, Farhaan (Department of Chemistry, 2025)
Methodological investigations for the efficient synthesis of two nitrogen-containing heterocyclic molecules are described; these molecules represent a significant portion of the natural and pharmaceutical world with functions implied in almost all biological processes, hence the necessity for their effective synthesis is of importance. Following an overview of the field in chapters one and two, the third chapter describes the development of a novel, Mn(OAc)3-mediated radical cyclisation-dimerisation cascade sequence for the synthesis of sterically challenging 3,3'-bisoxindoles using two complementary simple, acyclic starting materials; β-oxoanilines and β-oxoacids. This method proved amenable to a variety of modifications to the core molecule, with yields of up to 96% across over twenty substrates bearing a variety of functional groups. Mechanistic insights, based on an exhaustive optimisation study, showcasing an oxidation, de-carboxylation and biradical coupling cascade, forging three C-C bonds in a single step, are also presented. The second half of chapter three expands on the first, further developing the methodology towards an open-air, dual catalytic Manganese-Cobalt/Copper system. Substrate variation has been demonstrated with the synthesis of five analogues in yields of up to 70% as well biological evaluation of these molecules in vitro. The fourth chapter describes a unique, directed C(sp3 )-H functionalisation under mild photoredox conditions, using catalytic amounts of a base, a photocatalyst and 450 nm light to forge the biologically relevant indolyisoxazoline motif. Applicability of this functionalisation has been demonstrated via the synthesis of twenty substrates bearing various functional handles. To conclude, a mechanistic proposal has been presented based on optimisation and substrate data. Overall, this thesis provides an insight into the utility of both transition metal and photocatalysed radical chemistry and serves to deepen the understanding of the underlying mechanistic pathways for both.